Anterior segment dysgenesis (Peters' anomaly) in two snow leopard (Panthera uncia) cubs. (6th December 2012) - Hamoudi, Hassan; Rudnick, Jens‐Christian; Prause, Jan U.; Tauscher, Kerstin; Breithaupt, Angele; Teifke, Jens P.; Heegaard, Steffen
Abstract: Two sibling snow leopards, a male and a female, with bilateral anterior segment dysgenesis (ASD), are reported. Both snow leopards also had colobomas of both upper eyelids. All eyes exhibited a central corneal opacity associated with a defect in posterior corneal stroma, endothelium and Descemet's membrane. Iris strands were present attached to the termination of Descemet's membrane and to the periphery of the posterior corneal defect. The iris was hypoplastic, and cataract was present in all four eyes. The left eye of the female was microphthalmic, with no trabecular meshwork and with persistent remnant of the hyaloid artery. The male had hydrocephalus and thus some of the features of Peters' plus syndrome (Peters' anomaly in addition to systemic malformations). The histological findings in the eyes of these snow leopard siblings are identical with those described in humans with Peters' anomaly.